Transformational change in conservation - Toombs, Theodore Patrick, author; Knight, Richard L., advisor; Cross, Jennifer E., advisor; Teel, Tara L., committee member; Neimeic, Rebecca, committee member (Colorado State University. Libraries, 2021)
This dissertation explores a fundamental question for the conservation profession and society at large: How can we more effectively create the transformational change necessary to solve complex conservation problems? To do so, it's important to understand processes of transformational change and how they can be strategically utilized to address conservation problems. The lack of inclusion of social and systemic sciences into conservation science and practice hinders the profession's understanding of transformational change. Socio-ecological systems theory and social science have many insights to offer, but these insights have not been systematically incorporated into science and practice or coalesced into an integrated theory despite repeated appeals from social scientists. Each chapter of this dissertation takes a unique perspective on change. Chapter 2 explores the value orientations of Illinois farmers as important knowledge in the process of creating changes in individual behavior. Chapter 3 is a case study of conservation program that failed to materialize in part due to lack of attention to broader social issues. Chapter 4 is a synthesis of critiques of the current conservation paradigm that illustrate its bias toward individualistic, agentic theories of change that result from mainstream adoption of individual, neoliberal ideology. Many conservation problems are social and systemic in nature, yet the professions dominant theory of change is based on a theoretical perspective of these problems as individualistic, behavior problems. To address this, a more integrative set of theoretical perspectives is needed. Chapter 5 articulates a new, integrative theory of change (TTC) composed of four interdependent sets of mechanisms that can be enacted through strategic, conservation action in collaborative, place-based settings: (a) building communities of practice; (b) empowering individual catalysts; (c) reconfiguring the system; and (d) connecting across dimensions. I propose a set of testable propositions related to each of these components. The aim of the TTC is to integrate existing social and systems science insights into conservation science and practice, expand the set of potential interventions available, and improve the profession's ability to create the change necessary to address the world's most pressing conservation issues.
Keywords: neoliberalism; socio-ecological systems; value orientations; social change; conservation; systems change